CONCOMITANT JEJUNOILEAL AND COLONIC ATRESIAS - Muhammad Riazulhaq; Elbaqir Elhassan; Diaa Eldin Mahdi; Adel Mutawalli (EL-Med-Pub, 2012)
Intestinal atresia is fourth common cause of neonatal intestinal obstruction. Colonic atresia is relatively rare with an incidence of 1:40,000 to 1:60,000 live births. Coexisting jejunoileal and colonic atresias are scarcely described in literature.